COVID-19 and conflict. (April 2021) - Bloem, Jeffrey R.; Salemi, Colette
Highlights: We document trends in inter-group conflict at this historical moment. Globally, we see a dramatic short-term decline in conflict events as awareness of COVID-19 spread. This overall trend is mostly driven by a short-term decline in protest events globally. We also document critical heterogeneity and exceptions to this general finding. In some contexts inter-group conflict events have declined, in others these events have increased. Quantitative case studies highlight challenges in estimating robust causal estimates. Abstract: What does the threat of and the policy response to the coronavirus pandemic mean for inter-group conflict worldwide? We examine time series trends for different types of conflict and evaluate discernible changes taking place as global awareness of COVID-19 spread. At the country level, we examine changes in trends following policy responses, such as lockdowns, curfews, or ceasefires. We specifically examine violent conflict events (e.g., battles, remote violence and bombings, and violence against civilians) as well as civil demonstrations (e.g., protests and riots) using data from the Armed Conflict Location and Event Data (ACLED) project. Globally we see a relatively short-term decline in conflict, mostly driven by a sharp decrease in protest events, that has since recovered to pre-pandemic levels. Critical heterogeneity at the country level, however, persists. Finally, context-specific details challenge robust causal inference identifying the specific relationship between policy responses and conflict.